2016
DOI: 10.3109/09273948.2016.1160131
|View full text |Cite
|
Sign up to set email alerts
|

Acute Retinal Necrosis Presenting in Developmentally-delayed Patients with Neonatal Encephalitis: A Case Series and Literature Review

Abstract: We report three cases of patients with developmental-delay from neonatal herpetic encephalitis and/or meningitis who presented years later with acute retinal necrosis due to herpes simplex virus. The diagnosis was delayed in all cases due to the patients' inability to verbalize their ocular complaints and cooperate with eye examinations. This case series documents the clinical course, pathophysiologic mechanism, and treatment of acute retinal necrosis in this patient population. Clinicians should understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…There is no guidance based on large-scale data to guide decisions on the duration and dose of oral suppression/preventive therapy. Some experts recommend lifelong antiviral prophylaxis given that the onset of contralateral disease can occur after decades, at least for patients with a history of neonatal HSV encephalitis 8. Our literature review revealed marked variation in the duration of oral chronic suppression used in individual cases (table 1), though most of our reviewed case reports were published before the recent treatment guidance provided by the American Academy of Ophthalmology 6.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There is no guidance based on large-scale data to guide decisions on the duration and dose of oral suppression/preventive therapy. Some experts recommend lifelong antiviral prophylaxis given that the onset of contralateral disease can occur after decades, at least for patients with a history of neonatal HSV encephalitis 8. Our literature review revealed marked variation in the duration of oral chronic suppression used in individual cases (table 1), though most of our reviewed case reports were published before the recent treatment guidance provided by the American Academy of Ophthalmology 6.…”
Section: Discussionmentioning
confidence: 95%
“…Although uncommon, other cases of ARN associated with HSV encephalitis have been reported. A search of English PubMed articles about patients diagnosed with both ARN and HSV-1 or HSV-2 encephalitis revealed 34 case reports that are summarised in table 1 8-35. Median age was 44.5 years (range of 23 days to 68 years old) and male gender was reported in 24/36 (67%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…Half of the included patients had a history of herpes infection, making it an important and often reported diagnostic guidance element. 27 It is assumed that ARN occurs when immune dysfunction allows the herpes virus to reactivate. 29 It is of note that a third of patients included herein were immunosuppressed, which is higher than that reported in the literature.…”
Section: Discussionmentioning
confidence: 99%